Autobiographical Documentarism and Intertextuality in Ante Babaja’s Dobro jutro - Lučić, Krunoslav (Apparatus. Film, Media and Digital Cultures of Central and Eastern Europe, 2019)
The article analyses the problems of intertextuality, the autobiographical and the autofilmic in Ante Babaja’s documentary film Dobro jutro / Good Morning (2007, Croatia). In the first part, the piece outlines the general issues of intertextuality such as explicit and implicit intertextuality, citation, and allusion with examples from different national cinemas. The second part problematizes the interpretative horizon of the film’s genre which shares documentary, poetic, and essayistic traits with Babaja’s earlier films. In the last section, the three key strategies that Babaja uses to structure the specific universe of his last film are analysed. These include feigning impartiality and amateurism of the documentary approach to one’s life, the poetization of filmic expression with the tendency to reflect on death and bodily decrepitude, and the citation from films such as Kamenita vrata / The Stone Gate (1992, Croatia), Breza / The Birch Tree (Babaja, 1967, Yugoslavia), Miris, zlato i tamjan / Gold, Frankincense and Myrrh (Babaja, 1971, Yugoslavia), Izgubljeni zavičaj / Lost Homeland (Babaja, 1980, Yugoslavia), Tijelo / Body (Babaja, 1965, Yugoslavia), Pravda / Justice (Babaja, 1962, Yugoslavia) and Starice / Old Ladies (Babaja, 1976, Yugoslavia). Table of contents image from Dobro jutro / Good Morning (Ante Babaja, 2007, Croatia).